Effectiveness and harms of high-flow nasal oxygen (HFNO) for acute respiratory failure: a systematic review protocol. Issue 2 (12th February 2020) - Baldomero, Arianne K; Melzer, Anne; Greer, Nancy; Majeski, Brittany N; Macdonald, Roderick; Wilt, Timothy J
Abstract : Introduction: High-flow nasal oxygen (HFNO) use in adults hospitalised with acute respiratory failure (ARF) is increasing. However, evidence to support widespread use of HFNO compared with non-invasive ventilation (NIV) and conventional oxygen therapy (COT) is unclear. This protocol describes the methods for a systematic evidence review regarding the comparative effectiveness and harms of HFNO compared with NIV or COT for the management of ARF in hospitalised adult patients. Methods and analysis: We will search MEDLINE, Embase, CINAHL and Cochrane Library for randomised-controlled trials (RCTs) of adult patients hospitalised with ARF or who developed ARF while hospitalised. ARF will be defined as SpO2 <90%, PaO2 :FiO2 ratio ≤300, PaO2 ≤60 mm Hg, or PaCO2 ≥45 mm Hg. The intervention is HFNO (humidified oxygen, flow rate ≥20 L/min) compared separately to NIV or COT. The critical outcomes are: all-cause mortality, hospital-acquired pneumonia, intubation/reintubation (days of intubation), intensive care unit admission/transfers, patient comfort and hospital length of stay. The important outcomes are: delirium, 30-day hospital readmissions, barotrauma, compromised nutrition (enteral or parenteral nutrition), gastric dysfunction, functional independence at discharge and skin breakdown or pressure ulcers. We will calculate risk ratios and Peto ORs (for rare events) and corresponding 95% CIs for categorical outcomes. Mean and standardised mean difference will be calculated for continuous outcomes. Where possible and appropriate, meta-analysis will be performed for each outcome. Conclusion: This systematic review will provide a comprehensive evaluation of the evidence regarding the comparative effectiveness and harms of HFNO compared with NIV or COT for the management of ARF in hospitalised adult patients to inform clinical practice and to identify research gaps in the management of ARF in hospitalised adults. The results will inform the work of the American College of Physicians-Clinical Guidelines Committee in their development of a clinical guideline related to use of HFNO in adult patients with ARF. Ethics and dissemination: No ethical approval will be needed because we will be using data from previously published studies in which informed consent was obtained by the primary investigators. We will publish our results in a peer-reviewed journal. PROSPERO registration number: CRD42019146691